Estudo da origem e natureza dos sais em solos sódicos da região de Morada Nova, no Estado do Ceará - Gomes, Eisenhower Carvalho Braga (1991)
The studied area is located in a typically semi-arid region and partially emcompass the Morada Nova, Ibicuitinga, Banabuiú and Quixadá counties of the State of Ceará, between parrallels 4°58' and 5°11' S and meridians 38°39' and 38°33' W Gr. Results of morphological, physical, chemical and mineralogical characteristics are presented, taken from 17 (seventeen) samples of Solodic-Solonetz (Ustic Natrargids) and sodic Alluvial (Ustic Torrifluvents) soils. Three rock samples were analyzed, classified in relation to their nature and their mineralogical and ionic composition determined - the last one taken in the saturation extract - all according to the methodology adopted by EMBRAPA/SNLCS. From the results and interpretations, the soils were considered as weakly weathered, where feldspars and quartz predominate in the silt soil fraction, where mica, kaolinite and interstratified, not well defined clay minerals were also identified. Montmorillonite were recognized in the clay fraction of those soils. Chemical characteristics and properties suggest the denomination of "degraded sodic soils" with no carbonate content. Among soluble salts, NaCl predominates in the wholeness of the profile where, in minor proportions, chlorides, sulphates, and Mg and Ca bicarbonates were determined. Climate, substratum and topography constrain the effects of progressive concentrations of those salts in the soil, suggesting marine aerosols, as well as superficial and underground water elements contribution, as important additional sources to the sodification process.